Coping with Institutional Fragmentation? Competition and Convergence between Boundary Organizations in the Global Response to Polio - Anna Holzscheiter (Review of Policy Research, 2017)
This paper discusses competition and cooperation between boundary organizations (BOs) in the field of global health. It embeds its analysis of BOs in health in contemporary theories on institutional fragmentation and governance complexity, arguing that BOs in international politics have been a major driving force behind an often mind-boggling complexity of actors, institutions, and rule systems relevant to many contemporary international issues or “regimes.” The paper argues that growing complexity of global governance structures generates new demands for BOs with regard to how they manage their interactions with other BOs. Accordingly, the framework suggested in this paper builds on a set of hypotheses that do not isolate factors at structural and agent level but rather capture the interplay of BOs and their organizational environment. The paper's empirical analysis investigates two BOs, the Global Polio Eradication Initiative and GAVI, the Vaccine Alliance, working in the field of polio eradication.
Keywords: 330; global governance; health and medicine; boundary organizations; institutional complexity